Use of morphological and anatomical characters to delimit varieties of Paliurus spina-christi Mill. (Rhamnaceae) - Shahbaz, Saleem E.; Shareef, Nazar M. (Innovaciencia, 2018)
Introduction: Paliurus spina-christi Mill is a species with two varieties namely Paliurus spina-christi L. var. spina-christi and Paliurus spina-christivar. macrocarpa Beck native to mountains of Kurdistan, rarely growing in the upper plains of northern Iraq. Materials and Methods: A total of 15 plants from different parts of Kurdistan region were sampled. 30measurements for each characters of Leaf, Inflorescence, Flowers, Fruit, seeds, and leaf anatomical characters were measured for comparison between the two varieties. Results and Discussion: Fruit diameter of var. macrocarpa is significantly larger than fruit diameter of var. spina-christi. Most mean flower parts especially the ovary, in addition to seed size is larger in var. macrocarpa. Upper epidermal layer is always thicker than the lower epidermal layer for the same blade. The isobilateral mesophyll includes 2 layers of long palisade cells adaxially and 2-3 layers of short cells abaxially. Many vascular bundles are seen equally spaced in the mesophyll tissue.With the exception of the presence of simple hairs on the petiole adaxial side of the var. spina-cristi and the absence of these hairs from the same site of var. macrocarpa, all other anatomical features are considered to be of no taxonomic application. Stomatal density of the adaxial leaf side is up to 19 stomata per mm² in var. spina-christi while it is up to 38 stomata per mm² in var. macrocarpa. Conclusions: Both fruit diameter and the stomatal density of the adaxial leaf side constitute diagnostic characters for separating between the two varieties of Paliurus spina-christi Mill
Keywords: Paliurus spina-chriti L. var. spina-chriti, Paliurus spina-christi var. macrocarpa Beck., Isobilateral mesophyll, leaf anatomy, Petiole anatomy, Cuticular structure.